Direct time-domain channel impulse response estimation for OFDM-based systems - Ribeiro, C. (2012)
A method to estimate the channel impulse response using the received serial data in time-domain, without using DFT operations, is investigated. The processing required by the proposed method is substantially reduced when compared with LS-DFT channel estimation method, with no performance degradation. Furthermore, this method can incorporate the results of other published works that are DFT-based, at little or no added complexity, to improve the estimate of channel impulse response.